The effect of topical application of Malaysian honey on burn wound healing - Mohd Zohdi, Rozaini; Abu Bakar @ Zakaria, Md Zuki; Mohamed Mustapha, Noordin; Yusof, Norimah; Abdullah, Muhammad Nazrul Hakim (Veterinary Association Malaysia, 2004)
The efficacy of topical application of Malaysian honey on burn wound healing in Sprague-Dawley rats was investigated using 45 Sprague Dawley male rats weighing 200-300 g. Deep partial skin thickness burns were inflicted on the dorsal part of each animal. Two types of local honey (durian and Gelam) were applied twice a day in a quantity of 0.5 ml for each application, while control animals received no treatment. The rats were serially euthanisised at 3, 7, 14, 21 and 28 days post treatment for histological study. Histologically, early attenuation of inflammatory reaction and early reparative activities were observed in the honey treated wounds compared to control groups. Differential cells count showed a significant decreased in the number of inflammatory cells and increased vascularity in the honey treated wounds as early as 3 days post injury. In addition, epithelial regeneration appeared to be significant in gelam honey treated wound. This study showed that there was a significant acceleration of dermal repair in wound healing treated with durian and Gelam honey.